The Rise of the Roman Jurists - Bruce W. Frier (Princeton University Press, 2014)
Î™ HAVE TWO stories to tell. The first is the story of a lawsuit brought more than two millennia ago, and of the remarkable speech delivered during it; the second is the story of how, in the decades preceding and following this lawsuit, the legal profession originated and first rose to influence. My conviction, upon which this book is based, is that these two stories are interlinked, though not in a direct causal way; they are interlinked because neither story is completely comprehensible without the other. Cicero's speech pro Caecina was delivered during the third and final hearing of a lawsuit brought by Aulus Caecina probably in 69 B.C. Caecina, who had been named the principal heir of his late wife Caesennia, attempted to enter a farm allegedly within her estate. However, his way onto the farm was barred by Sextus Aebutius, who had organized a band of armed men to defend the farm's perimeter. Caecina then brought suit against Aebutius under the interdict de vi armata, in order to "recover" possession of the farm. Throughout the ensuing trial Cicero spoke on Caecina's behalf; and he later published, perhaps in a somewhat altered form, his final speech for his client. I have long been interested in the pro Caecina. First of all, this speech, which is probably Cicero's last effort before the civil bar, is exceptionally fine; Cicero himself regarded it as a masterpiece of its kind, and later critics both ancient and modern have shared that judgment. It is therefore a pity that, because of its subject matter, the speech is so little known among most students of Roman literature. Further, the pro Caecina is the only one of Cicero's four surviving private orations that is also complete, and no private oration by any other Roman orator comes down in more than small fragments. This fact alone gives the pro Caecina a considerable historical importance.